Indigenous Rights in Venezuela and the Problem of Recognition - Orellano, Jorge (2016)
The recognition of indigenous rights in the Constitution of Venezuela 1999 represents a conceptual tension in the way of conceiving the citizenship: means transit of a homogeneous citizenship to other multicultural character. However, the realization of those rights has found practical difficulties relating to land titling, lack of political backing for indigenous interests, conflicts with the armed forces, among others, that do lose sight of the conceptual problems underlying the recognition and the construction of citizenship. The aim of this trial, based on a hermeneutic methodology and supported in discourse analysis of documentary sources, will be present some reflections on conceptual tensions that underlie problems of realization of indigenous rights in Venezuela in the last decade, in particular those related to the construction of a multicultural citizenship.The main findings include overlapping assimilation and false recognition that has incurred the current institutional regime and we conclude pointing the need to move forward in an intercultural concept to surpass mere multicultural condition of indigenous rights coupled with the necessary impulse of a representative democratic framework for a genuine recognition and full citizenship.